ANALISIS FAKTOR-FAKTOR DOMINAN DALAM PEMBENTUKAN CREATIVE TOURISM DAN PENGARUHNYATERHADAP KEPUTUSAN BERKUNJUNG (Survei terhadap Wisatawan Mancanegara Asal Belanda, Jerman dan Perancis yang berkunjung ke D.I. Yogyakarta) - Supriatna, Dendi; Wibowo, Lili Adi; Yuniawati, Yeni (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
This research try to find factor to create creative tourism toward visiting decision, research try to find factors can develop european tourist visiting decision to Daerah Istimewa Yogyakarta. Creative tourism have seven variabels latent creative architecture, creative design, creative fashion, creative culinary, creative music, creative performing art, and creative fine art. Used 107 respondent included Netherland, France and Germany who collect from systematic random sampling (mobile sampling) and calculated by confirmaty factor analysis and Structural Equation Modeling, Researcher find 5 to create creative tourism factor: creative architecture, creative design, creative fashion, creative culinary, creative performing art,and the 5 factor of creative tourism can influence toward visiting decision are creative architecture, creative design, creative fashion, creative culinary have positive effec towards visiting decision.